Peritoneal rent: No hindrance to completing eTEP - Srishti Swarupa; Bharti, Vikeerna; Leesa Misra; Nivedita Sahoo; Manash Ranjan Sahoo; Sreeparna Ghosh (Asian Journal of Medical Sciences, 2024)
Background: Extended view total extraperitoneal (eTEP) has rapidly gained popularity over the last decade. Peritoneal rent during surgery is another complication that makes surgery difficult and forces surgeons to convert to either transabdominal pre-peritoneal or open hernioplasty. With our approach despite peritoneal rent developed intraoperatively, surgery can be completed in the same extraperitoneal plane during eTEP. Aims and Objectives: The primary objective of this study was to investigate the feasibility of completing eTEP surgery despite the occurrence of peritoneal rent during the procedure. Materials and Methods: It is a retrospective case series conducted at high volume center, All India Institute of Medical Science, Bhubaneswar, where eTEP is performed on regular basis for patients with inguinal hernia. While performing eTEP, we came across 10 cases where peritoneal rent developed intraoperatively and was repaired using 2–0 vicryl following which eTEP was successfully completed. Results: Six patients out of 10 underwent peritoneal rent repair through the extraperitoneal approach, with an average operative time of 97.5 min. The repair process added an average of 12.5 min to the standard eTEP operative time of 85 min. Four patients underwent peritoneal rent repair through the intraperitoneal approach, with a mean operative time of 120 min. This approach added approximately 35 min to the surgery, reflecting the additional time required for the intraperitoneal repair. Conclusion: Our findings suggest that peritoneal rent developed during eTEP surgery can be effectively managed without compromising the integrity of the procedure. Repairing the peritoneal rent extraperitoneally takes advantage of the wide extraperitoneal space provided by the eTEP approach, offering flexibility in port placement and enhanced ergonomics. Alternatively, intraperitoneal repair with additional ports is a viable option. Peritoneal rent should not be perceived as a hindrance to the successful completion of eTEP surgery. This innovative approach expands the scope of eTEP by providing solutions for unforeseen complications, ensuring its continued efficacy in inguinal hernia repair.